PENGARUH STRATEGI PEMBELAJARAN PHYSICAL SELF ASSESSMENT DENGAN MODEL JOYFUL LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM - Annisa Putri; zona octarya; yuni fatisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
AbstractThis research was instigated by Chemistry subject at State Senior High School 1 Siak Hulu that was dominated by Lecturing method, and the low of student scores on Atomic Structure lesson in the Academic Year of 2016/2017. This research aimed at knowing the effect of Joyful Learning model with Recitation method using Physical Self-Assessment learning strategy toward student learning achievement on Atomic Structure lesson. Experimental method was used in this research with True experimental pretest posttest control group design. Purposive sampling technique was used in this research. The samples were the tenth-grade students of Natural Science 1 as the experimental group and the students of Natural Science 2 as the control group. The used instruments were learning achievement test that was supported by observation sheet and documentation. The research findings showed that tobserved score 2.74 and ttable was 2.00. It showed that tobserved was higher than ttable, there was an effect on learning achievement, and the effect was 11.5%. So, it could be concluded that there was an effect of Joyful Learning model with Recitation method using Physical Self-Assessment learning strategy at State Senior High School 1 Siak.Keywords: Joyful Learning Model, Recitation Method, Physical Self-Assessment Learning Strategy, Learning Achievement, Atomic Structure